2022
DOI: 10.1021/acs.orglett.2c00805
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed C(sp3)–C(sp3) Cross-Electrophile Coupling of In Situ Generated NHP Esters with Unactivated Alkyl Bromides

Abstract: The formation of C(sp 3 )−C(sp 3 ) bonds by crosscoupling remains a challenge in synthesis. Here, we demonstrate a two-step, one-pot protocol for the in situ generation of Nhydroxyphthalimide esters and their nickel-catalyzed cross-electrophile coupling with unactivated alkyl bromides for the construction of 1°/1 °C(sp 3 )−C(sp 3 ) bonds. The conditions tolerate an array of functional groups, and mechanistic studies indicate that both substrates are converted to alkyl radicals during the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Our group has recently explored the use of modified NHP esters in couplings with alkyl halides, but the reason for their improved reactivity had not been determined. [30] We have found that a combination of solvent effects and NHP ester tuning can improve yields with aryl bromides by slowing the rate of radical generation (Scheme 2). Methyl and methoxy-substituted NHP ( Me NHP and MeO NHP) esters are more difficult to reduce (shifts in E p of 10-50 mV, Scheme 2A and Figures S2-S4) and are consumed more slowly under reducing conditions (0.1 equiv ZnBr 2 with Zn reductant, Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has recently explored the use of modified NHP esters in couplings with alkyl halides, but the reason for their improved reactivity had not been determined. [30] We have found that a combination of solvent effects and NHP ester tuning can improve yields with aryl bromides by slowing the rate of radical generation (Scheme 2). Methyl and methoxy-substituted NHP ( Me NHP and MeO NHP) esters are more difficult to reduce (shifts in E p of 10-50 mV, Scheme 2A and Figures S2-S4) and are consumed more slowly under reducing conditions (0.1 equiv ZnBr 2 with Zn reductant, Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…We envisioned that altering the reduction potential of redox‐active esters would enable us to tune their rate of consumption, thereby providing a new avenue to control the selectivity profile of this coupling. Our group has recently explored the use of modified NHP esters in couplings with alkyl halides, but the reason for their improved reactivity had not been determined [30] . We have found that a combination of solvent effects and NHP ester tuning can improve yields with aryl bromides by slowing the rate of radical generation (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, alkyl‐substituted carboxylic acids and primary amines are two of the cheapest and most abundant class of building blocks in organic chemistry [16–20] . These compounds can be conveniently activated to obtain stable but redox‐active electrophiles [ N ‐(acyloxy)phthalimides (NHPI esters) [13a–e] and pyridinium salts, [14] respectively], which are known to serve as alkylating agents in cross‐coupling processes. Accordingly, we speculated if aliphatic NHPI esters and pyridinium salts can serve as partners to couple with glycosyl halides stereoselectively, which would furnish our desired C ‐alkyl glycosides in a straightforward fashion.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, several emerging horizons are beginning to surface that can capitalize on these versatile starting materials: for example, an electrochemically driven reductive double DCC for the synthesis of a multitude of structures via a convergent C­(sp 3 )–C­(sp 3 ) coupling (Figure ). , The ramifications for such a method to simplify retrosynthetic logic are enormous, as practically any carbon–carbon bond can be retrosynthetically cleaved with this transform. As an example, unnatural amino acid 8 was previously prepared in an eight-step sequence involving a pyridine hydrogenation-based strategy where no C–C bonds were forged .…”
mentioning
confidence: 99%